Experiences of pregnancy and perinatal healthcare access of women who are deaf: a qualitative study. (4th October 2022) - Panko, Tiffany L.; Cuculick, Jess; Albert, Sasha; Smith, Lauren D.; Cooley, Margarita M.; Herschel, Melanie; Mitra, Monika; McKee, Michael
Abstract: Objective: Women who are deaf experience higher rates of reproductive healthcare barriers and adverse birth outcomes compared with their peers who can hear. This study explores the pregnancy experiences of women who are deaf to better understand their barriers to and facilitators of optimal pregnancy‐related health care. Design: Qualitative study using thematic analysis. Setting: Semi‐structured, individual, remote or in‐person interviews conducted in the USA. Sample: Forty‐five women who are deaf and communicate using American Sign Language (ASL) and gave birth in the USA within the past 5 years participated in the interviews. Methods: Semi‐structured interviews explored how mothers who are deaf experienced pregnancy and birth, including access to perinatal information and resources, relationships with healthcare providers, communication access and their involvement with the healthcare system throughout pregnancy. A thematic analysis was conducted. Main outcome measures: Barriers and facilitators related to a positive experience of perinatal care access among women who are deaf. Results: Three major themes emerged: (1) communication accessibility; (2) communication satisfaction; and (3) healthcare provider and team support. Common barriers included choosing healthcare providers, inconsistent communication access and difficulty accessing health information. However, when women who are deaf were able to use ASL interpreters, they had more positive pregnancy and birth experiences. Self‐advocacy served as a common facilitator for more positive pregnancy and healthcare experiences. Conclusions: Healthcare providers need to be more aware of the communication and support needs of their patients who are deaf, especially how to communicate effectively. Increased cultural awareness and consistent provision of on‐site interpreters can improve pregnancy and birth experiences for women who are deaf. Abstract : Linked article : This article is commented on by Moreland et al., pp.522–523 in this issue. To view this mini commentary visit https://doi.org/10.1111/1471-0528.17362 This paper has a Video Abstract presented by Jenna Stewardson, Deaf Health Laboratory Research Program Coordinator at the NTID Research Center on Culture and Language available at: https://vimeo.com/761853406 .